2020
DOI: 10.4038/seajme.v13i2.206
|View full text |Cite
|
Sign up to set email alerts
|

Objective structured practical examination (OSPE) versus viva voce: the Indian students’ and faculty perception

Abstract: Introduction: In most of the medical colleges in India, practical examination in Anatomy is conducted in the form of conventional viva-voce. Viva-voce is however limited by its lack of validity, reliability and objectivity. Objective Structured Practical Examination (OSPE) has been proposed as objective, reliable and valid method of assessment. The present study was conducted to assess the feasibility of conducting OSPE in our setup and to determine perception of first year undergraduate medical students and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…21 A study revealed that students preferred OSPE examination more than viva examination, as there is no examiner stress, no bias, and enough time to think and come up with the correct answer. 22 The current study revealed that the students considered embryology a subject that required more time for deeper understanding, followed by gross anatomy. Perhaps, they found the developing anatomy more complicated than the other sub-disciplines of Anatomy.…”
Section: Discussionmentioning
confidence: 76%
“…21 A study revealed that students preferred OSPE examination more than viva examination, as there is no examiner stress, no bias, and enough time to think and come up with the correct answer. 22 The current study revealed that the students considered embryology a subject that required more time for deeper understanding, followed by gross anatomy. Perhaps, they found the developing anatomy more complicated than the other sub-disciplines of Anatomy.…”
Section: Discussionmentioning
confidence: 76%